La actualidad del concepto de sobrenaturaleza de José Ortega y Gasset: una mirada desde la inteligencia artificial (2020)
The first texts in which José Ortega y Gasset reflected on the technique were published in 1935. It has been almost a century and this text intends to rescue one of the concepts that the Spanish philosopher presented in Meditation on technique, namely supernatural. At present, the great challenge that technology has imposed has been to take its maximum exponent to artificial intelligence, to make it a challenging means of the limits that nature imposes on us. Among the most outstanding proposals within the field of artificial systems is superintelligence and uniqueness, two of the desires most longed for by thinkers such as Nick Bostrom or Raymond Kurzweil. So, if the technological field is focusing great efforts on the development of artificial intelligence, we should ask ourselves if the motivation behind such an impulse is truly based on the human need for a supernatural that Ortega y Gasset talked about so much.